2021
DOI: 10.1530/ec-21-0154
|View full text |Cite
|
Sign up to set email alerts
|

Childhood reproductive hormone levels after pediatric hematopoietic stem cell transplantation in relation to adult testicular function

Abstract: Objectives: Longitudinal assessment of testicular function after pediatric hematopoietic stem cell transplantation (HSCT) is needed to guide clinical follow-up. We investigated dynamics in male reproductive hormones after pediatric HSCT, focusing on pubertal timing and associations with testosterone deficiency and azoospermia in adulthood. Methods: This retrospective, longitudinal study included 39 survivors median 19 years after pediatric HSCT. Serum concentrations of LH, testosterone, FSH, and inhibin B fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 33 publications
0
12
2
Order By: Relevance
“…Previous follow-up studies after childhood cancer treatment or allogeneic HSCT reported higher LH and FSH levels, low-normal T levels, and lower INHB and anti-Müllerian hormone levels at adulthood, compared to the general population. [22][23][24]31 Mathiesen et al 23 highlighted T deficiency in early adulthood after pediatric HSCT that was associated with higher LH levels from mid-puberty onwards.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous follow-up studies after childhood cancer treatment or allogeneic HSCT reported higher LH and FSH levels, low-normal T levels, and lower INHB and anti-Müllerian hormone levels at adulthood, compared to the general population. [22][23][24]31 Mathiesen et al 23 highlighted T deficiency in early adulthood after pediatric HSCT that was associated with higher LH levels from mid-puberty onwards.…”
Section: Discussionmentioning
confidence: 99%
“…This is a four‐fold increase compared to the earlier reported international survey from 2012 9 . In recent years, small‐scale long‐term follow‐up studies after high‐risk gonadotoxic treatment have been conducted, some of which focusing on HSCT 21–24 . However, not only the gonadotoxic treatment, but also the testicular biopsy itself could have an impact on gonadal function and future fertility.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations